Determining the high temperature performance grade and workability of styrene-butadiene-styrene modified bituminous binders according to superpave system - Yilmaz, Mehmet; Kök, Baha Vural (My University, 2008)
Various deterioration primarily rutting occurs on hot mix asphalt at high temperatures unless using suitable binder. Hot mix asphalts have to be mixed and compacted at specific temperatures in order to exhibit high performance. The polymer originated additives have been used to extend the service life of pavement by preventing the failures which will occur in pavement. The mixing and compaction temperatures can be identified by determining the resistance to rutting parameter at high temperatures using the experiments of dynamic shear rate (DSR) and rotational viscosimeter (RV) which are in superpave system. In this study the effect of styrene-butadiene-styrene (SBS), which is used for bitumen modification, on high temperature performance and workability of bitumen binders was investigated. The modified binders were obtained with adding three different SBS content (2%,4%,6%) to 100/150 penetration grade bitumen. The mixing and compaction temperature of mixtures were determined applying the rotational viscometer (RV) experiment to neat and modified asphalt. The neat and modified binders were aged according to RTFOT method. The high temperature performance levels of binders were determined according to Superpave system by carried out dynamic shear rheometer (DSR) test on binders before and after aging processes. Based on the obtained results it was determined that the mixing and compaction temperatures increased with the increase of SBS content. Furthermore it was determined that the G*/sin? which is a parameter of high temperature resistance increased with the increase of SBS content for both aged and unaged binders according to results of DSR test.
Sti?ren-butadi?en-sti?ren modi?fi?yeli? bi?tümlü ba?layicilarin superpave si?stemi?ne göre yüksek sicaklik performans sevi?yesi?ni?n ve i?şlenebi?li?rli??i?ni?n beli?rlenmesi?
Keywords: Bitumen; Dynamic shear rheometer; Rotational viscosimeter; SBS; Superpave